Impacts of high-speed rail on airlines, airports and regional economies: A survey of recent research - Zhang, Anming; Wan, Yulai; Yang, Hangjun (Transport policy, 2019)
This paper first reviews studies on the impacts of air-HSR competition on airlines, focusing on the overall effects of parallel HSR services on passengers' mode choice as well as on airlines’ flight frequency, traffic volume, fares, service quality and market power. The modal complementarity and air-HSR intermodal services, together with the network feature of airline business, are also examined. The paper then reviews theoretical and empirical findings on the impacts of HSR on airports and regional economies. Here, the main insights include: First, HSR can have a traffic redistribution effect on airport traffic; in particular, some primary hub airports with good air connectivity may gain traffic while others may lose traffic. Second, to mitigate congestion at hub airports, policy makers may consider diverting some traffic to regional airports by promoting air-HSR intermodal services. Third, as HSR may stimulate long-haul/international air traffic, its overall impact on emission reduction remains unclear. Finally, similar to the impacts on airport traffic, spatial disparity of economic activities may also rise after the introduction of HSR. In general, the disparity tends to rise between the cities with HSR and those without HSR, as the former gets better accessibility. However, among the cities with HSR services, the disparity between the large and small cities could increase or decrease depending on several factors. •Impacts of high-speed rail on airlines and airports are reviewed.•HSR can have a traffic redistribution effect on airport traffic.•Spatial disparity of economic activities may rise after the introduction of HSR.•The disparity tends to rise between the cities with HSR and those without HSR.